Nitrogen, sulfur-codoped micro–mesoporous carbon derived from boat-fruited sterculia seed for robust lithium–sulfur batteries. Issue 28 (20th May 2019) - Wu, Jian; Zhang, Qi; Li, Mo; Yan, Jian; Zhang, Yong; Liu, Jiaqin; Wu, Yucheng
Abstract : Physical confinement and chemical adsorption of polysulfides on boat-fruited sterculia seed derived nitrogen, sulfur-codoped micro–mesoporous carbon for robust lithium–sulfur batteries. Abstract : The diverse textures and tunable surface properties of abundant bioresources offer great opportunities to utilize biochar materials as sulfur hosts for naturally boosting the electrochemical performances of Li–S batteries. Herein, a N, S-codoped micro–mesoporous carbon was synthesized from boat-fruited sterculia seed, and used as a sulfur host matrix for Li–S batteries. After sulfur infiltration (≈62% sulfur) and cell assembly, the obtained S/NSBC cathode shows outstanding discharge–charge performance, good rate capability, and especially long cycling stability. A high initial discharge capacity of 1478 mA h g −1 was achieved at 0.1C, and the reversible discharge capacity was still retained at 649 mA h g −1 after 500 cycles at 0.5C with ultralow decay rate of 0.08% per cycle, and especially zero-capacity-decay after 300 cycles. Such superior electrochemical performance of S/NSBC cathode is attributed to the synergy of the unique 3D conductive micro–mesoporous frameworks and huge N, S-codoped polar surface within the carbon matrix, which can physically confine the dissolved polysulfides within the pore structures, and chemically anchor the polysulfides through chemical interaction between lithium polysulfides and N and S sites, thus enabling the favorable reaction kinetics, efficient utilization of sulfur, and effective mitigation of polysulfide diffusion and shuttling within the cathode. This work well manifests the great feasibility and superiority of utilizing bioresources for high performance Li–S batteries.